Water Quality Index of Well Water in the Converted Agricultural Land - Prabowo, R.; Bambang, A. N.; Sudarno, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
The groundwater condition at converted agricultural land has decreased water quality because of previous agricultural processes, so the water quality index is essential to know. This study aims to measure the groundwater quality index in residential wells on the converted agricultural land, determine the dominant parameters that form the Water Quality Index (WQI) in dug wells and drilled wells on the converted agricultural land, and determine the effect depth and age of wells on WQI. The research design was descriptive exploratory with WQI as the dependent variable and the depth and age of the well as the independent variable. With purposive sampling, 32 points of dug and drilled wells in different locations were chosen. Multiple linear regression was applied for data analysis. From the findings, it can be concluded that the minimum WQI value in dug well water is 76.9, and the average maximum WQI value in dug well water is 92.3. There are 8 points in dug well water with WQI in a good category or quality-2 category (71-90), and 15 dug well points have WQI in a very good quality category or quality-1 category (91-100). This value indicates that the dug well water quality in the research location is still classified as eligible for consumption. The dominant parameters that form WQI values in dug and drilled wells are manganese, cadmium, iron, with a value of -0.918 -0.886 -0.790. The depth and age of the well affect the water quality index. The depth of the well has a stronger effect on the water quality index than the age of the well.